Complex network theory and game theory-based partitioning decision-making of parallel restoration for resilient power grid - Wei, Xin; Pan, Lianrong; Xie, Daiyu; Yang, Sheng; Wei, Boyao (Frontiers in Energy Research, 2024)
The ability of fast restoration reflects power system resilience and safety. This paper proposes a partitioning decision-making method for parallel restoration based on the label propagation algorithm and the cooperative game theory. The topological and physical characteristics of blackout systems are considered as the edge weight and the node importance simultaneously for formulating the partitioning model. By the label propagation algorithm, various labels representing different subsystems mark all buses. To accelerate the speed of convergence and prevent the label oscillation, this paper proposes a game strategy of cooperation between buses and subsystems by evaluating the Shapley value of buses. The partitioning constraints are integrated into each label propagation process to assess the feasibility of the partitioning strategy. Finally, case studies on the IEEE 39-and 118-bus test systems and an actual urban power system in South China verify the effectiveness of the proposed method.